Children's Linguistic Repertoires Across Dialect and Standard Speech: Mirroring Input or Co-constructing Sociolinguistic Identities?. Issue 1 (2nd January 2022) - Kaiser, Irmtraud
ABSTRACT: The present study analyses 3- to 6-year-old children's dialect-standard repertoires in an Austrian-Bavarian sociolinguistic setting and investigates how far individual repertoires can be explained by input and sociodemographic factors. Adults' linguistic repertoires in the area typically comprise a certain spectrum on the dialect-standard continuum but individual acquisition processes have hardly been studied yet. We collected language data from 49 children in five different communicative interactions each and analyzed the repertoire each child exhibits. The majority of children could be shown to have a bi-varietal repertoire at their disposal, but there were substantial numbers of children who exhibited either standard-only or dialect-only repertoires. We then examined the relationships between a child's repertoire and potentially relevant input and sociodemographic variables. While language variety use in the home and maternal education did not prove significant predictors of children's repertoires, gender, age, location, bilingualism and frequency of being read to did.